Communication Strategy for the Regeneration of New Members in the Bina Vokalia Choir of SMA Negeri 2 Bandar Lampung - Wisnu, Laras; Waskito, Budhi; Verawati, Noning (Interaction Communication Studies Journal, 2025)
This study explores the communication strategies used in the regeneration of new members in the Bina Vokalia Choir at SMAN 2 Bandar Lampung. Triggered by a decline in membership and achievements from 2018 to 2023, this research employed a qualitative descriptive method using in-depth interviews, observation, and documentation. A SWOT analysis approach was used to identify internal and external factors influencing recruitment and adaptation of new members. Findings indicate that personal interest in music, peer influence, organizational reputation, and persuasive communication from seniors play critical roles in students’ decisions to join. The study concludes that a combination of interpersonal and persuasive communication, consistent mentoring, and reinforcement of group identity enhances effective regeneration. These findings provide practical insights for managing school-based extracurricular arts organizations.